A categorical data analysis of impact of biogas on women of rural households – with examples from Nepal - Jyoti U. Devkota (International Journal of Advances in Applied Sciences, 2019)
This paper is based on primary data collected from 400 households of biogas consumers. A detailed structured questionnaire was developed and pretested. Here response to each question was given as a multiple choice option resulting in more than 450 categorical data. These variables studied various aspects of households using biogas. The results focused on women of these households. Interrelationships between several other variables including the role of a woman in various decisions related to the plant were analyzed. Logistic regression of decision making of woman on several variables including asset index of the family was done. This asset index was calculated from the principle component analysis of socio-economic variables. The family dynamics in the choice of biogas as renewable energy source was quantified using odds ratio and regression coefficients. The interdependence between variables was tested using Chi square test of Independence of Attributes. A novel data based approach of generation and analysis of categorical data is demonstrated here. The suitability of generation of categorical data in the absence of accurate measurement instruments is highlighted. This method is also suitable for countries without a strong backbone of good quality official records, and provides a good backup data for official statistics.